RM das articulações sacroilíacas: novos parâmetros para diferenciação entre espondiloartrite axial e alterações mecânicas ou degenerativas - Castro Junior, Moacir Ribeiro De [UNIFESP] (2019)
Objective: To evaluate SPARCC index score, Apparent Diffusion Coefficient (ADC) values and topography of Sacroiliac Joint (SIJ) lesions for ability to distinguish Axial Spondyloarthritis (AS) from Mechanical Sacroiliac Joint Disease (MSIJD). To compare the performance of detection of BME in Short Tau Inversion Recovery (STIR), Diffusion Weighted Imaging (DWI) and postcontrast T1 Fat-Saturated (T1FSGD) sequences. Method: SIJ MRI scans of 34 patients with subchondral BME conducted from 2012 to 2016 were analyzed retrospectively. Seventeen had been diagnosed with AS (Group I) and 17 with MSIJD (Group II). Two radiologists evaluated the presence and topographic distribution of the BME lesions in SIJ, calculated the SPARCC index score, the ADC values of the BME lesions and of the bone marrow of the interforaminal sacral region. They also assigned scores from 1 to 5 to the BME lesions by evaluating the signal or enhancement in the sequences described above. Results: SPARCC index cutoff value of ≥8.5 offered the best accuracy for differentiation between AS and MSIJD, with scores ≥8.5 indicating AS and scores <8.5 indicating MSIJD. Predictive values were: 79.4% accuracy, 64.7% sensitivity, 94.1% specificity, 91.7% positive predictive value and 72.7% negative predictive value. In AS, the frequency of inflammatory lesions was significantly higher on the iliac surfaces compared to the sacral surface (p=0.015). Among the AS iliac lesions, a significantly higher proportion was observed in the upper ilium third as compared to middle and lower thirds (p=0.040). Mean ADC values in the BME lesions were 1.16x10-3mm2/s and 1.03x10-3mm2/s in patients with AS and 1.06x10-3mm2/s and 1.03x10-3mm2/s in patients with MSIJD; on diffusion maps, 600 and 1000 respectively. The mean values of ADC of the bone marrow of the interforaminal sacral region were 0.50x10-3mm2/s and 0.39x10-3mm2/s, on each map. The mean value of the scores attributed by the examiners to the BME areas did not show significant differences in the Wilcoxon test. The intraclass correlation coefficients were high (0.791, 0.876, 0.880, 0.907 and 0.713 for STIR, DWI b=50s/mm2, DWI b=600s/mm2, DWI b=1000s/mm2 and postcontrast T1 FAT-SAT, respectively). The mean value of the scores attributed to the STIR sequence was the highest, followed by the decreasing order of DWI with b=50s/mm2, T1FSGD, DWI with b =600s/mm2 and DWI with b=1000s/mm2. The mean scores of the different sequences showed statistically significant differences, except between the DWI b=600s/mm2 and T1FSGD (p=0.059). The comparison between the mean scores attributed to the STIR sequence and the DWI sequence with b=50s/mm2 showed p=0.007; all other comparisons presented p<0.001. Conclusions: The SPARCC index can be used for the differentiation between EA and MSIJD. There was also a predominance of EA lesions on the iliac surface, more frequently on its upper third. Mean values of ADCs found in the areas of BME were greater than the mean values of the bone marrow of the interforaminal sacral region. However, these values did not allow the differentiation between EA and MSIJD. DWI presented better performance for detecting subchondral BME, as compared to T1FSGD.